A Jungian Approach to Analytic Work in the Twenty‐First Century. (February 2014) - Cochrane, Maggie; Flower, Steven; Mackenna, Chris; Morgan, Helen
<x xml:space="preserve">Abstract</x> In Part 1 of this paper the authors summarize those key concepts in Jungian analytic theory which differentiate it from a psychoanalytic approach. To illustrate these perspectives and their application in clinical work, a patient is introduced. The authors elaborate on a particular dream with the proposition that it holds within it both an image of the internal world of the patient's personal psyche and something which might be viewed as archetypal and emerging from the collective unconscious. Part 2 focuses on more recent developments in Jungian analytic thinking. Michael Fordham's important work in extending Jungian theory into an understanding of infant development is summarized and illustrated by a clinical example. This is followed by a brief summary of how contemporary debate within the Jungian analytic community has been much affected by recent developments in areas outside the analytic discourse which have offered both a challenge to and an affirmation of certain Jungian concepts. Examples given are from emergence theory and neuroscience. The Jungian interest in such phenomena stems from a view of the human psyche as rooted in a wider world of matter, culture, history and an unconscious that is not only personal but also collective.